Striped flea beetle, Phyllotreta striolata : status and management in radish - K.V., Raghavendra; Balodi, Rekha; Chander, Subhash; H.R., Sardana (Indian Farming, 2022)
Flea beetles [Phyllotreta striolata (Fabricius)] are the most abundant and harmful coleopteran pests of cruciferous vegetables causing considerable yield loss in many countries. For the past two years, striped flea beetle, Phyllotreta sp. infestation was found to be very serious on radish and mustard crops in different villages of Haryana and Delhi. The marketability of the produce was hampered due to the pest and the infested radish roots (edible part) fetched very low prices in the market leading to severe economic loss to the farmers. To combat the pest problem in radish, Integrated Pest Management (IPM) interventions were validated at Samora village of Nilokheri block in Karnal district of Haryana, in Farmers’ Participatory Mode. It was observed that the IPM fields performed better in comparison to the non-IPM fields, in terms of reduction in pest damage and avoidance of unwarranted insecticide application and also fetched more prices in the market than the radish grown in non-IPM fields. Altogether, farmers obtained a higher yield of quality products by following IPM interventions in radish in the study area. Farmers fetched higher prices in the market and were satisfied by the IPM interventions.